Translation Analysis of Circumstances in the Gospel of Matthew Chapter 12 through 14 from English into Indonesian - Tilusubya, Burwan; Nababan, Mangatur; Santosa, Riyadi (Lingua Cultura, 2018)
This research deployed translation of circumstances, viewed from transitivity with the descriptive qualitative method. Its objectives were to describe the translation technique of the circumstances and to evaluate the quality of the translation based on accuracy and acceptability. It utilized document analysis and focus group discussion for data collection. The data were analyzed through the domain, taxonomy, componential analysis, and finding cultural value. Meanwhile, the research indicates the application of established equivalent, combination, modulation, transposition, paraphrasing, deletion, explicitation, discursive creation, and implicitation techniques are influenced by the form of a circumstance or an adverb. Furthermore, the application of established equivalent, combination, and implicitation produces a good translation based on accuracy compared to modulation, transposition, explicitation, and paraphrasing. The research concludes that the deployment of appropriate translation techniques produces a good translation.